Pengaruh Harga, Kualitas Produk, dan Lokasi Terhadap Minat Beli di Porong Wei - Adamas Samjaya, Stefanie; Soesanto, Jesselyn; Grasielda, Ivana (Program Magister Manajemen STIE Widya Wiwaha Yogyakarta, 2025)
Consumer puchase intention is a crucial determining factor in business success, especially in the highly competitive food and beverage industry. Entrepreneurs in the food and beverage industry must be able to increase and maintain consumer puchase intention to sustain and grow their business. If consumer puchase intention declines, the business may face serious threats that could lead to losses and even failure. Based on this, this research was conducted to examine the influence of price, product quality, and location on puchase intention at Porong Wei Signature Pakuwon Mall Surabaya. Using purposive sampling, 130 respondents from Surabaya, consisting of those who had and had not visited Porong Wei Signature Pakuwon Mall Surabaya, participated in this study. Data analysis was conducted using multiple linear regression and SPSS version 26 software to test validity, reliability, classical assumptions, and research hypotheses. The results show that price and location variables have a significant positive effect on consumer puchase intention, while product quality has a positive but insignificant effect. The findings of this study provide important implications for entrepreneurs and marketers to develop marketing strategies to increase consumer puchase intention.